Historical Research in the Low Countries 1970–1975 - Carter, Alice C. author. aut Link
VIII, 276 p.
Keywords: The five review articles included in this volume were produced by the Dutch History Seminar of the University of London with the assistance of several Belgian and Dutch historians. They first appeared in the volumes VI-X of the Acta Historiae Neerlandicae (in 1978 renamed The Low Countries History Yearbook), a periodical published by the Dutch Historical Society with the objective of bringing new pUblications on the history of the Low Countries in the Dutch language to the attention of English-speaking historians. These articles have been republished and provided with indexes in the hope that in this form they will also prove to be useful to students of Belgian and Dutch history who have not been regular readers of the Acta. Should this pUblication be favourably received a subsequent volume covering the years 1976-1981 may be issued. THE EDITORS VII Survey of recent Dutch Historiography ALICE C. CARTER, Editor INTRODUCTION This bibliographical article has been put together by members of the Dutch history seminar held at London University's Institute of Historical Research. The article is intended for non-Dutch-reading scholars and indeed all who are interested in Netherlands history. An attempt has been made, and will continue to be made, to survey important works published in the year previous to that in which the article is drawn up. This year we have concerned ourselves with books or in the earlier part of 1971.